Carbon Sequestration during Restoration of Degraded Hills by Rainwater Harvesting and Afforestation in Rajasthan, India - Singh, G. (Indian Forester, 2017)
Carbon storage in both soils and vegetations was assessed after six years of restoration work in degraded hills involving rainwater harvesting (RWH), afforestation and regeneration. There were seventy-five 700 m2 plots laid in <10%, 10-20% and >20% slopes of a degraded hills with different RWH treatments like Contour trench (CT), Gradonie (GD), Box trench (BT), V-ditch (VD) and a control without RWH. Conducing environmental conditions and soil resource availability under RWH influenced carbon sequestration in both plants and soils. After 65 months of restoration highest amount of carbon accumulated in trees, shrubs and bamboo was in <10% slope, herbaceous vegetation in 10-20% slope and soils in >20% slope. Effects of RWH was indicated by enhanced carbon by 20.8-46.0% in tree, 73.3-96.4% in shrubs, 75.0-109.2% in bamboo, 15.9-70.5% in herbaceous vegetation and 10.1-18.7% in soil compared with control. Amount of carbon sequestered during restoration in plants and soils was 4.18 and 29.90 tons (t) ha in >20% slope to 8.81 and 21.1 t ha-1 in <10% slope, respectively. Effects of RWH enhanced standing biomass carbon by 50.6% in GD to 72.3% in VD, and soil carbon by 13.9% in GD to 23.2% in CT plots over control. Rate carbon sequestration in standing biomass and soils were highest in <10% and >20% slope, respectively. Lowest rate was in control for both plants and soils. The rate was highest in VD plots (1.28 t ha-1 y-1 ) for standing carbon and CT plots (5.24 t ha-1 y-1 ) for soil carbon. Conservation of soil and water through RWH and afforestation enhanced per cent soil and SOC and thus carbon stock positively and at higher rate. Thus restoration of degraded hills applying RWH and afforestation appeared beneficial in sequestering carbon and can be adopted under mitigation option of climate change.